Prevalence of symptoms of musculoskeletal disorders related to self-reported work Dentistry student and professors (Research, Society and Development, 2021)
Work-related musculoskeletal disorders (WMSD) is the generic name given to a set of heterogeneous affections that affect muscles, joints, and nerves, which can appear in individuals submitted to certain working conditions. Therefore, the present study aimed to verify the prevalence of WMSD symptoms in dentistry students and professors. To assess WMSD symptoms, the Brazilian version of the Nordic Musculoskeletal Symptoms Questionnaire (QNSO) was used, applied to a sample of students and professors from the dentistry course. To understand the data, a descriptive analysis of the data was performed. Five hundred five (n=505) individuals participated in the study, 75% female and 25% male. Of the total respondents, 30% reported a workday of six hours, 51% a workday of up to eight hours, and 19% a workday of more than eight hours. Regarding musculoskeletal pain, 76% of the sample reported pain in the cervical and lumbar region with some frequency. The preliminary results of the present study support the hypothesis that WMSD symptoms may begin as early as the graduation of dentistry students, often in the cervical and lumbar regions.